The Influence of Debt To Equity Ratio and Earning Per Share on Share Prices in Coal Mining Sub-Sector Companies Listed on the Indonesian Stock Exchange in 2020-2023 - Risma Ariyani; Cecep Hermana (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Availability of funds is a component that supports industrial sustainability. Industry can obtain funds easily by offering shares to the public through the capital market. This condition will directly influence activities in the capital market, which in turn influences the amount of demand and supply on the stock exchange and has an impact on share price fluctuations. Low share prices can motivate investors to buy more shares. The average share price in the mining subsector from 2020 to 2021 experienced a significant increase, from 2022 to 2023 there was a significant decrease due to negative sentiment for the coal subsector, where Indonesia's largest coal consumer, one of which is China, reduced demand for Coal exports and Europe reduce demand for coal. The aim of this research is to find out and analyze the influence of the Debt to Equity Ratio on stock prices, to find out Earning Per Share on stock prices, and to find out jointly the effect of Debt to Equity Ratio and Earnings Per Share to share price. The population in this study are coal mining sub-sector companies listed on the IDX. This research uses a quantitative approach with sample determination, namely purposive sampling and obtained 10 companies as research samples over a 4 year period, namely 2020-2023, thus using 40 financial reports. The data analysis method used is multiple regression analysis with partial and simultaneous hypothesis testing using SPSS as data processing. The research results simultaneously state that DER and EPS have an effect on stock prices. Partially, DER has no effect on share prices. EPS influences share prices.